(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2024)
Medico-legal autopsies are a cornerstone of forensic investigations, providing insight into the causes and circumstances of unnatural deaths. Objective: This study aims to delineate the patterns of unnatural deaths, focusing on suicides and accidental deaths over a five-year period. Methods: We conducted a retrospective analysis of 1,461 medico-legal autopsies performed from 2018 to 2022 at a medical college in Haryana. The data were examined for trends in the cause and manner of death.Results: The retrospective analysis revealed that suicides were the most common manner of death among the cases studied, surpassing accidental deaths. Poisoning was identified as the leading cause of mortality, followed closely by fatalities resulting from road traffic accidents. The demographic data indicated a higher prevalence of these incidents among males aged 31- 40 years. Conclusion: The study provides a detailed examination of the predominant causes of unnatural deaths in Haryana, highlighting the critical need for preventive measures against suicides and accidental deaths, particularly those resulting from poisoning and road traffic accidents.